2013
DOI: 10.1186/1759-8753-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly diverse chromoviruses of Beta vulgaris are classified by chromodomains and chromosomal integration

Abstract: BackgroundChromoviruses are one of the three genera of Ty3-gypsy long terminal repeat (LTR) retrotransposons, and are present in high copy numbers in plant genomes. They are widely distributed within the plant kingdom, with representatives even in lower plants such as green and red algae. Their hallmark is the presence of a chromodomain at the C-terminus of the integrase. The chromodomain exhibits structural characteristics similar to proteins of the heterochromatin protein 1 (HP1) family, which mediate the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 79 publications
(100 reference statements)
3
56
0
Order By: Relevance
“…Not only were the most abundant quinoa copia - rt clones pCquty119/pCquty118 preferentially located in pericentromeric heterochromatin, but also the overall retrotransposon density was higher in pericentric regions (as evidenced from FISH with pooled rt regions, excluding pCquty119/pCquty118) than in subterminal chromosomal regions. Similar pericentromeric localization was reported for two Ty3- gypsy retrotransposons Beetle ( CRM/CR lineage) and Bingo1 ( Reina ) in B. vulgaris chromosomes (Weber et al 2013). However, other Ty3- gypsy elements showed different chromosomal organization in Beta .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Not only were the most abundant quinoa copia - rt clones pCquty119/pCquty118 preferentially located in pericentromeric heterochromatin, but also the overall retrotransposon density was higher in pericentric regions (as evidenced from FISH with pooled rt regions, excluding pCquty119/pCquty118) than in subterminal chromosomal regions. Similar pericentromeric localization was reported for two Ty3- gypsy retrotransposons Beetle ( CRM/CR lineage) and Bingo1 ( Reina ) in B. vulgaris chromosomes (Weber et al 2013). However, other Ty3- gypsy elements showed different chromosomal organization in Beta .…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, in the genomes of species of the genus Beta closely related to Chenopodium, several abundant Ty1- copia [Cotzilla1 ( Sire/Maximus ), SALIRE1 ( Tork/TAR ), Weber et al 2010] as well as Ty3- gypsy retroelements were reported [Bongo3 ( Del/Tekay ), Beetle7 ( CRM/CR ), Bingo1 ( Reina ), Weber et al 2013; Elbe3 ( Athila ), Wollrab et al 2012]. The copy number of individual LTR retroelement families in plant genomes can vary greatly from very few copies to thousands of copies (Du et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main Gypsy lineages are OGRE/TAT, large LTR-REs with an open reading frame located upstream of the gag gene (Neumann et al 2003); Athila, first reported in Arabidopsis thaliana (Wright and Voytas 2002); and Chromovirus, a lineage of REs carrying a chromodomain at the 5′ end of the coding portion, which is especially abundant in centromeres (Gorinsek et al 2004;Llorens et al 2011). In certain species, chromoviruses were further subdivided into four sublineages (Galadriel, Tekay, CR, and Reina), based on the relative positions of the chromodomain and a polypurine tract (PPT), and on the LTRs length (Weber et al 2013). On the other hand, Copia REs can belong to many different lineages, the most frequent being AleI/Retrofit/Hopscotch, AleII, Angela, Bianca, Ivana/Oryco, TAR/Tork, and Maximus/SIRE (Wicker and Keller 2007).…”
mentioning
confidence: 99%
“…One widespread group of Gypsy retrotransposons, the so-called chromoviruses or CRM clade, is interesting for the presence of chromodomains at the C-terminus of the IN (Gorinsek et al 2005). The chromodomain is similar to domains of heterochromatin protein 1 (HP1), which may confer particular integration patterns to some chromoviruses (Weber et al 2013). Phylogenetic and sequence analysis of members of the CRM clade in plants (Neumann et al 2011), defined one particular group that contains a CR motif similar that found in the chromodomain-bearing MAGGY retrotransposons of fungi (Gao et al 2008) and is concentrated in centromeric regions.…”
Section: Ltr Retrotransposon Replication and Growth In Genome Sizementioning
confidence: 99%